Evaluating the impacts of climate disasters and the integration of adaptive flood risk management - Al-Amin, A.Q. (2020)
Climatic change and its related impact are among the most challenging threats facing the world at present. Most developing countries are particularly vulnerable to the impact of climate change due to their economic circumstances. As such, they are often less able to implement adaptation strategies to reduce climate-related impact. Based on this, this study deals with the risk, vulnerability and adaptive measures in the case of sudden disasters (i.e. heavy floods and tsunami) by applying the disaster vulnerability approach, using a case study in Malaysia. This study applies three basic indicators of climatic disasters' impact and issues – (i) flood disaster vulnerability (Ω); (ii) flood disaster magnitude (Π); and (iii) integration of adaptive flood risk management (§) using public risk perception of climate disasters and flood prevention strategies. Following the findings, this study proposes procedural and theoretical frameworks which are comparatively new to the research of climate threats (climate change, variability and disasters). Additionally, it offers decision makers' valuable insights which may assist in promoting greater awareness of flood risk management, in both Malaysia and other communities facing similar climate threats and disaster trends. © 2019 Elsevier Ltd